Exergy analysis of the revolving vane compressor unit - Na, Yong Tat (Nanyang Technological University, 2022)
This project aims to perform an exergy analysis on the Revolving Vane Compressor unit and study the second law efficiency of the Revolving Vane Compressor for refrigeration applications using exergy analysis. The total exergy destruction rate can be divided into four categories: friction, heat transfer, adiabatic throttling, and fluid mixing. Losses in the revolving vane compressor unit can then be analyzed according to these aspects so that improvements and enhancements can be recommended. A computer simulation program, Fortran, is used to simulate the exergy analysis to identify the exergy destruction in the revolving vane compressor. R1234yf is the working fluid used for the computer simulation. A parametric study is conducted on the operating speed and the different types of refrigerant to determine how these parameters will affect exergy destruction rate due to heat transfer, friction, fluid mixing, and adiabatic throttling. The 2nd law of efficiency of the compressor is then computed to see what the best operating speed is suitable for the compressor and also to determine the most compatible refrigerant based on the environmental impact on the environment and also the 2nd law of efficiency. From the parametric study, it was concluded that the higher the operating speed, the better the 2nd law of efficiency, and also the R1234yf is the most suitable refrigerant to be used for the revolving vane compressor unit due to its least environmental impact and highest 2nd law of efficiency as compared to the other refrigerants. Therefore, R1234yf can be considered to have great potential to work as the refrigerant in the future.